"THE INFLUENCE OF WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE WITH MENTAL HEALTH AS AN INTERVENING VARIABLE: A STUDY AT LPP RRI JAMBI" - Isfa, Salsabila; Adriani, Zulfina; Setiawan, Wahyu Juari (Journal of Business Studies and Management Review, 2025)
This study aims to examine the effect of work-life balance on employee performance with mental health as an intervening variable at LPP RRI Jambi. A quantitative method was applied using a survey approach by distributing questionnaires to 62 employees. Data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results indicate that work-life balance has a significant positive effect on both mental health and employee performance. Moreover, mental health significantly mediates the relationship between work-life balance and employee performance. These findings highlight the importance of creating a supportive work environment that fosters work-life balance to enhance employees’ mental health and overall productivity.